ANALISIS KETERAMPILAN DASAR MENGAJAR GURU DALAM MELAKSANAKAN PEMBELAJARAN DI SEKOLAH DASAR - Bastian Bastian (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2019)
This research was conducted at SD Neger 022 Pulau Baru Kopah, Sentajo Raya District. The purpose of this study was to find out how the basic teaching skills of teachers at SDN 022 Pulau Baru Kopah. The subjects in this study were 15 class teachers, consisting of 4 male teachers and 11 female teachers. Judging from the problems discussed about describing the basic skills of teaching teachers in implementing learning, this study belongs to a descriptive quantitative study. Descriptive quantitative research is a method that examines a group of people, an object, a system of thought or an event in the present. The results showed that the basic teaching skills of teachers at SD Negeri 022 Pulau Baru Kopah obtained an average grade of 76.9 in the good category. Broadly speaking, it can be concluded that the use of basic teaching skills of teachers in the implementation of learning has been classified as good.